Development of algorithm to calculate rational rolling schedule on a blooming - Бондаренко, Юлія Володимирівна (Technology audit and production reserves, 2015)
Modern blooming is a powerful assembling mill. One of the key factors that determines the performance of blooming is the rolling mode which includes a compression mode and speed modes of the working cage. Though, the greatest impact on performance is done by compression mode. It has been determined, that calculation of the mode compression can effectively be carried out by one of the key factors, i.e. acceptable capture angle. The resulting preliminary compression mode should be adjusted on the basis of engine’s power, rolls durability, the degree of stability in caliber staffs, and according to the necessary final dimensions of the blooming. The new method of calculation as well as the block diagram of rolling on blooming mill is shown in the article. The algorithm for computing the rational modes of compression during rolling on blooming mill is presented. It is shown, how the method simulates the process of blooming and allows you to choose the scheme based on rolling steel mark, the conditions of capturing and the number of passes. Algorithm calculates the compression mode according to the canting scheme. The block diagram is given, that allows determining the minimum number of passes when rolling on blooming mill.